Automotive industries in developing countries - Baranson, Jack. ([Washington, International Bank for Reconstruction and Development]; distributed by the Johns Hopkins Press, Baltimore, 1969)
This study is concerned with the relative cost and efficiency of manufacturing various types of transport equipment under the conditions that prevail in newly industrializing economies The study also provides a framework which could be used for economic analysis of industrial projects I other economic sectors.
Bibliographical footnotes.
osa 22/01/19
Loans
Keywords: Automobile industry and trade; Developing countries